2012
DOI: 10.21161/mjm.43912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different growth conditions on certain biochemical parameters of different cyanobacterial strains

Abstract: Aims: Variation in the traditional growth medium conditions to enhance the production of lipids, carbohydrates, protein and the free amino acids content of three cyanobacterial species. Methodology and Results: Three species of cyanobacteria (Anabaena laxa, Anabaena fertilissima and Nostoc muscorum) were collected from the culture collection of Soils, Water and Environment Research Institute, Agriculture Research Center, Giza, Egypt, to investigate their biochemical composition under different growth condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
7
1
Order By: Relevance
“…While performance and body temperature results are reliable because they are based on a fair number of replicates and rectal temperature measurements, respectively, speculations about mortality data must be made cautiously due to the modest number of birds per pen, which has made mortality rate a variable very susceptible to change in this trial. Data from the literature suggest that arginine supplementation could help broilers counteract the detrimental effects of HS on growth performance (Hassan et al, 2021;Teyssier et al, 2022). Nevertheless, our results seem to contradict that performance of heat-stressed broilers benefits from this nutritional strategy.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…While performance and body temperature results are reliable because they are based on a fair number of replicates and rectal temperature measurements, respectively, speculations about mortality data must be made cautiously due to the modest number of birds per pen, which has made mortality rate a variable very susceptible to change in this trial. Data from the literature suggest that arginine supplementation could help broilers counteract the detrimental effects of HS on growth performance (Hassan et al, 2021;Teyssier et al, 2022). Nevertheless, our results seem to contradict that performance of heat-stressed broilers benefits from this nutritional strategy.…”
Section: Discussioncontrasting
confidence: 75%
“…The reasons for testing arginine supplementation as a potential nutritional strategy for HS alleviation are as follows. First, it has been demonstrated that diet composition and environmental conditions considerably influence arginine requirement of broilers (Khajali and Wideman, 2010;Hassan et al, 2021). In this regard, precise and consistent arginine requirements for broilers under HS are not readily available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Tannins have been suggested to be involved with antibacterial and anti-viral activity while tannins and flavonoids are thought to be responsible for antidiarrheal activity (Adisa et al, 2004;Enzo, 2007;Adisa et al, 2010). Saponins are known to possess both antimicrobial (Soetan et al, 2006) and anti-inflammatory activities (Hassan et al, 2012). Studies have also reported the beneficial effects of saponins on blood cholesterol levels and stimulation of the immune system (Cheeke, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of Enzymatic Antioxidants. We assessed the activities of ascorbate peroxidase (APX), POX, glutathione peroxidase (GPX), SOD, and CAT following the methods reported by Hassan et al (2012) 24 . Sprouts were homogenized (MagNA Lyser, Germany) in 1 mL of KPO 4 buffer (50 mM, pH 7.0) containing 10% PVP, 0.25% Triton X-100, 0.001 PMSF, and 0.001 M AsA.…”
Section: Experimental Designmentioning
confidence: 99%